2021
DOI: 10.1111/1365-2435.13824
|View full text |Cite
|
Sign up to set email alerts
|

A dormant amoeba species can selectively sense and predate on different soil bacteria

Abstract: Soil protists are the invisible majority of soil eukaryotes, which are essential but often forgotten parts of the soil ecosystem. They play key roles in microbial food webs by predating on other soil microbes. However, it is not clear how dormant soil protists sense, recognize and feed on diverse microbial prey. In this study, we used a soil amoeba, Dictyostelium discoideum, to study selective discrimination and predation of 14 different bacteria. We found that discrimination and sensing of prey in D. discoide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 81 publications
(92 reference statements)
0
12
0
Order By: Relevance
“…Consequently, D. discoideum has an instinctive response to feed on bacteria or acquire symbionts from the complex environment. Recent studies indicate an intense preference for Gram-negative compared to Gram-positive bacteria ( 30 ). However, our study showed that all tested Burkholderia bacteria could attract amoebas, but the cells could not distinguish symbiotic and nonsymbiotic Burkholderia bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, D. discoideum has an instinctive response to feed on bacteria or acquire symbionts from the complex environment. Recent studies indicate an intense preference for Gram-negative compared to Gram-positive bacteria ( 30 ). However, our study showed that all tested Burkholderia bacteria could attract amoebas, but the cells could not distinguish symbiotic and nonsymbiotic Burkholderia bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…For example, our previous studies found that dormant D. discoideum could selectively sense and prey on different soil bacteria based on their density and nutritional value. 3 In addition, bacterial size and mobility out of the prey spectrum of the predator can avoid being preyed on by amoeba. 55 In this study, D. discoideum showed preference predation for S. decolorationis S12, while it could not feed on B. laterosporus.…”
Section: ■ Discussionmentioning
confidence: 99%
“…laterosporus, S. decolorationis S12, and a mixture with the same OD value and bacterial suspension volume . The experimental design with four different bacterial densities (OD 600 = 0.2, 0.6, 1.0, and 1.8) provides comprehensive and reliable information about how D.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations